Pattern of distribution of different salivary gland tumors; a retrospective study in NICRH, Dhaka (Bangladesh Journal of Medical Science, 2016)
Background: Salivary gland tumors are rare, generally benign and affect both major and minor salivary glands.Objective: To find out the pattern of distribution of different benign and malignant salivary gland epithelial tumors and their relation to age and sex in a tertiary care center in Bangladesh.Methodology: This is a retrospective study. Details of epithelial salivary gland tumors were obtained from department of ENT, National institute of cancer & research hospital (NICRH), Dhaka, Bangladesh from the period January 2009 to December 2012 (3 years).Result: A total number of 261 cases presenting with both benign and malignant salivary gland tumors were analyzed according to gender, age and histopathological findings. There were 130 (49.84%) males and 131 (50.19%) females with the male female ration of 1: 0.99. Age of study population ranged from 10 to 70 years with the mean age 40.78. Percentage of benign salivary gland tumors was 73.94% and malignant salivary gland tumor 26.05%. Among major salivary gland tumors, no sublingual tumors were found and parotid gland tumors were the commonest. Whereas, among minor salivary gland tumors palatal minor salivary tumors were common.Conclusion: Parotid gland was the most common site of origin of both benign and malignant salivary gland tumors. Histopathologically, pleomorphic adenoma was the most common benign salivary gland tumor and mucoepidermoid carcinoma was the most frequent malignant neoplasm. Adenoid cystic carcinoma was common minor salivary gland tumor.Bangladesh Journal of Medical Science Vol.15(1) 2016 p.90-94